Analysis of Demand and Supply of Money Supply on Economic Growth - Simanungkalit, Jelita; Diani, Salma; Rahmi, Siti Naila; Fitrawaty, Fitrawaty (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research examines the relationship between monetary aggregates (M1 and M2) and economic growth as measured by nominal Gross Domestic Product (GDP) in Indonesia during the period of January-June 2024. The research aims to analyze the impact of money demand and supply on economic growth using multiple linear regression analysis. Research findings reveal that the model has an explanatory capability of 71.6% in explaining nominal GDP variations. Key findings include: (1) M1 has a negative relationship with nominal GDP, with a regression coefficient of -3.240, indicating that an increase in narrow money supply is associated with a decline in GDP. This can be caused by resource diversion effects from productive sectors and lag effects in monetary policy transmission; (2) M2 shows a significant positive relationship with nominal GDP, with a regression coefficient of 9.363, indicating that an increase in broad money supply correlates with economic growth.